Analisis Komparatif Stereotip Budaya Madura Oleh Etnik Jawa Di Desa Jaddung Pamekasan - Nur Azizah, Mei; Hazin, Muhammad; Mariyam, Siti (Meyarsa: Jurnal Ilmu Komunikasi dan Dakwah, 2023)
This research will discuss the process of forming Madurese cultural stereotypes and the prejudices of Javanese ethnic men or women who married Jaddung villagers before and after living in the Madura region. Stereotypes are an interesting discussion because they can become obstacles in the communication process so that they can lead to negative judgments between tribes and ethnicities. This research method is included in comparative quantitative research. This quantitative research contained lumerical data and was processed using statistical methods. With a comparative approach, namely to determine the level of approach of a variable from two different groups. This research is associated with the study of symbolic interaction theory which has 3 elements, namely Mind, self and society. The results of the study show that there is a Javanese perspective in looking at the characteristics of Madurese before carrying out marriages. Madurese are known to be hard, rough, and when faced with problems they are resolved by means of gauze (carok), but this changes when they are married. In their view, they see that the Madurese have very close characteristics and solidarity and kinship.